2022
DOI: 10.3390/e24070927
|View full text |Cite
|
Sign up to set email alerts
|

Rolling Bearing Fault Diagnosis Based on WOA-VMD-MPE and MPSO-LSSVM

Abstract: In order to further improve the accuracy of fault identification of rolling bearings, a fault diagnosis method based on the modified particle swarm optimization (MPSO) algorithm optimized least square support vector machine (LSSVM), combining parameter optimization variational mode decomposition (VMD) and multi-scale permutation entropy (MPE), was proposed. Firstly, to solve the problem of insufficient decomposition and mode mixing caused by the improper selection of mode component K and penalty factor α in VM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Some of this method’s advantages are that it has fewer parameters to adjust, and its simplicity makes it easy to implement and combine with other optimization strategies. This stochastic method imitates the behavior of large populations of individuals, moving through the “hyperspace of the possible solutions”, evaluating the input data as the coordinates of their position in the objective Equation (fitness) and sharing information of the best results with each other [ 36 ].…”
Section: Numerical Methodologymentioning
confidence: 99%
“…Some of this method’s advantages are that it has fewer parameters to adjust, and its simplicity makes it easy to implement and combine with other optimization strategies. This stochastic method imitates the behavior of large populations of individuals, moving through the “hyperspace of the possible solutions”, evaluating the input data as the coordinates of their position in the objective Equation (fitness) and sharing information of the best results with each other [ 36 ].…”
Section: Numerical Methodologymentioning
confidence: 99%
“…In this study, the optimization capability of particle swarm optimization (PSO) is selected to optimize the parameters of LSSVM [19][20][21] so as to further improve the model performance. The PSO algorithm updates its own speed and position after each iteration according to the optimal solution of the particle itself and the global optimal solution.…”
Section: Improved Lssvm By Particle Swarm Optimizationmentioning
confidence: 99%
“…Experiments have shown that the method proposed in this paper has good diagnostic performance. In addition, some other researchers have used algorithms such as the fruit fly optimization algorithm [15], the sparrow search algorithm (SSA) [16] and whale optimization (WOA) [17] to determine the optimal number of decomposition k layers. Although better results were achieved by using various optimization algorithms to determine the k-value, the optimization algorithms need to determine many parameters, such as: batching and number of iterations, and the selection of batching and number of iterations will seriously affect the decomposition efficiency of VMD [18].…”
Section: Introductionmentioning
confidence: 99%